Tobacco smoking and trends in histological subtypes of female lung cancer at the Cancer Hospital of the Chinese Academy of Medical Sciences over 13 years - Zeng, Qiang (Thorac Cancer, 2019)
BACKGROUND: Lung cancer is the leading cause of cancer mortality among women in China, and incidence and mortality continue to rise despite the fact that smoking prevalence is very low among Chinese women. AIM: This study investigated tobacco smoking and trends in histological subtypes of female lung cancer in a central cancer hospital in China. METHODS: Demographic, smoking history and histological information on female lung cancer patients diagnosed or treated from 2000 to 2012 was collected from the Cancer Hospital, Chinese Academy of Medical Science (CHCAMS). The classification of histological subtypes and clinical stages were conducted using the ICD‐O‐3 and Eighth AJCC Cancer Staging Manuals. Time‐trends of histological subtypes were analyzed based on annual percentage change (APC). RESULTS: Overall, 5870 female cases of lung cancer were included in the analysis. The number of female lung cancer patients increased from 509 (2000–2002) to 1744 (2011–2012). The most common histological type of lung cancer was adenocarcinoma (ADC) (72.93%), followed by small cell lung cancer (SCLC) (11.06%), squamous cell carcinoma (SCC) (8.38%) and other (7.63%). Among smokers, the proportion of SCC decreased from 40.5% to 23.7% (P = 0.005), while ADC increased from 35.7% to 50.7% (P = 0.009). In non‐smokers, ADC increased from 63.1% to 80.6% (P = 0.006) and SCC decreased from 13.6% to 4.5% (P = 0.016). Among SCC cases, smokers made up a larger proportion of early stage (I/II: 47.1%) compared with late stages (III, 34.3%; IV, 18.6%). CONCLUSION: The number of female lung cancer patients has increased in CHCAMS. In both smoking and non‐smoking cases, the proportion of adenocarcinoma increased. Squamous cell carcinomas were more likely to be diagnosed in early stages among smokers.